FORMATION OF OCCUPATIONAL SAFETY COMPETENCE IN FUTURE ENGINEERS - Rakhimov Oktyabr Dustkabilovich; Chulieva Munisa (Bright Mind Publishing, 2025)
The article presents analytical information on the meaning and areas of use of the terms competence and competence, components of the professional competence of an engineer. The role of occupational safety competence in the development of the professional competence of an engineer and the requirements for developing its model are discussed.
Keywords: Competence, competence, approach, professional, occupational safety, model, knowledge, skills, motive.